(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
Printed electronics (PE) is an emerging technology under the umbrella of additive manufacturing that uses functional inks to print circuits and electrical components on various substrates. The enormous potential of PE can be envisioned in applications ranging from soft robotics, smart textiles to healthcare. The talk will discuss droplet?based printing techniques (inkjet, aerosol jet, and electrohydrodynamic jet) used to enable next-generation devices. It is important to access surface roughness, porosity and surface tension that will influence ink-substrate interactions for good printability. The talk will showcase our research on building library of printable inks with various functionalities and our efforts in fabricating novel device architectures on unconventional substrates. The limiting factors and challenges of printed electronics that hinder their commercializing and mass adoption will also be discussed. Shweta Agarwala is tenure-track Assistant professor at Department of Engineering, Aarhus University, Denmark and heads ‘Printed Electronics Technology’ laboratory. Her research focuses on using printed technology route to enable next-generation, biocompatible and biodegradable electronics and healcare devices. Through her research, she is trying to understand interaction of electronic inks on unconventional substrates like paper, textiles, polymers, medical plasters and biomaterials. She obtained her Master’s at the prestigious Nanyang Technological University (Singapore) and later defended PhD at National University of Singapore (Singapore). She was a postdoc at the Energy Research Institute in Singapore, and later went to Singapore Centre for 3D Printing to pursue research in printed electronics before travelling to Denmark. Shweta is author of more than 50 peer-reviewed papers published in internationally renowned journals, books and conferences. She serves as the chair of IEEE Women in engineering Denmark section.